Implementing the Managerial Values of the Prophet Rasullah SAW in the Management of Contemporary Islamic Education - Sri Mayang Mandra; Salsabila Azizah; Muslim Afandi (Journal of Practice Learning and Educational Development, 2025)
This article aims to explore and analyze the implementation of the managerial values of Prophet Muhammad SAW within the framework of contemporary Islamic education management. The Prophet is recognized not only as a messenger of Allah but also as an exemplary leader and manager who successfully established a civilized society based on divine guidance and universal humanitarian values. This study adopts a qualitative-descriptive approach through a literature review of both classical and modern references, including works by George R. Terry, Imam Machali, and Mujamil Qomar. The findings indicate that the leadership principles of Prophet Muhammad SAW—such as shiddiq (truthfulness), amanah (trustworthiness), tabligh (communication), fathanah (wisdom), as well as musyawarah (consultation) and istiqamah (consistency)—greatly contribute to building effective and ethical Islamic educational leadership. These values remain highly relevant for today’s educational leadership in facing globalization, moral decline, and the challenges of digital transformation. By adopting the Prophet’s prophetic values as a managerial and educational role model, Islamic educational institutions can achieve governance that is both professional and spiritual. Therefore, mainstreaming these prophetic managerial values is a strategic necessity for navigating contemporary educational dynamics.